2012
DOI: 10.1002/j.0022-0337.2013.77.4.tb05487.x
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Relationship Between Emotional Intelligence and Dental Student Clinical Performance?

Abstract: Emotional intelligence has emerged as a key factor in differentiating average from outstanding performers in managerial and leadership positions across multiple business settings, but relatively few studies have examined the role of emotional intelligence in the health care professions. The purpose of this study was to examine the relationship between emotional intelligence (EI) and dental student clinical performance. All third-and fourth-year students at a single U.S. dental school were invited to participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 31 publications
2
78
0
1
Order By: Relevance
“…They additionally added that many professional behaviors in health care may require abilities related to EI as: putting the patient needs ahead of their individual interests, fight to complete tasks at high standard nearly at all times, frequently assess their knowledge and skills, be familiar with their limitations and act with integrity. [5] The psychologists Salovery and Mayer first used the word EI in 1990. They defined it as "the ability to process emotion-laden information competently and to use it to direct cognitive behavior as problem solving and to spotlight energy on requisite behaviors".…”
Section: Introductionmentioning
confidence: 99%
“…They additionally added that many professional behaviors in health care may require abilities related to EI as: putting the patient needs ahead of their individual interests, fight to complete tasks at high standard nearly at all times, frequently assess their knowledge and skills, be familiar with their limitations and act with integrity. [5] The psychologists Salovery and Mayer first used the word EI in 1990. They defined it as "the ability to process emotion-laden information competently and to use it to direct cognitive behavior as problem solving and to spotlight energy on requisite behaviors".…”
Section: Introductionmentioning
confidence: 99%
“…Future studies that could involve the other outcome variables, such as patient satisfaction and clinical performance of the dentists are also needed. (20) It was found in our study that the students had an average emotional intelligence that was significantly associated with academic performance. The EI levels have to be further improved, by making sure that every dental college has regular counselling and personality development classes along with the normal curriculum that will help them develop a positive attitude and manage their stresses well.…”
Section: Limitations Of the Studymentioning
confidence: 52%
“…The mental health (Bolsoni-Silva & Loureiro, 2015b, Adlaf et al, 2001 and social skill variables (Aguilhar, 2008;Artino et al, 2012;Burgess, Roberts, Black & Mellis, 2013;Fernandez et al, 2012;Gomes & Soares, 2013;Iturra et al, 2012;Victoroff & Boyatzis, 2013) were also related to the final academic performance. Social skills appear to be protective for good academic and social development of the university students Fernandez et al, 2012;Gomes & Soares, 2013;Iturra et al, 2012;Victoroff & Boyatzis, 2013) and divergent findings from Del Arco (2005). Data from other studies have shown that school and courses variables also influence the social skills repertoire (Al-Alawneh el al., 2011;Artino et al, 2012;Bolsoni-Silva & Loureiro, 2015b;Gomes e Soares, 2013) and, additionally, that social skills influence the mental health of the university student (Angélico et al, 2012;Bolsoni-Silva & Loureiro, 2014;Segrin, 2000).…”
Section: Discussionmentioning
confidence: 96%
“…Analyzing these data in light of the literature showed that characteristics of the course and sociodemographic variables were identified as predictors of academic performance (Aguilhar, 2008;Iturra et al, 2012;Lópes-Bárcena et al, 2009;Oliveira et al, 2008). The mental health (Bolsoni-Silva & Loureiro, 2015b, Adlaf et al, 2001 and social skill variables (Aguilhar, 2008;Artino et al, 2012;Burgess, Roberts, Black & Mellis, 2013;Fernandez et al, 2012;Gomes & Soares, 2013;Iturra et al, 2012;Victoroff & Boyatzis, 2013) were also related to the final academic performance. Social skills appear to be protective for good academic and social development of the university students Fernandez et al, 2012;Gomes & Soares, 2013;Iturra et al, 2012;Victoroff & Boyatzis, 2013) and divergent findings from Del Arco (2005).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation